The letters of C. Vann Woodward - Woodward, C. Vann (Comer Vann), 1908-1999 (Yale University Press, 2013)
C. Vann Woodward was one of the most prominent and respected American historians of the 20th century. He was also a very gifted and frequent writer of letters, from his earliest days as a young student in Arkansas and Georgia to his later days at Yale when he became one of the arbiters of American intellectual culture. Presented here are his sprightly, wry, sympathetic, and often funny letters, including those he wrote to figures as diverse as John Kennedy, David Riesman, Richard Hofstadter, and Robert Penn Warren.